Green Tea Leaves And Peanut Shells As Biosorbents For Removal Of Chromium (Vi) And Nickel (Ii) Ions From Aqueous Solution - M B Ramesh Kumar, Dhivesh (2020)
This study was aimed to compare the relative removal efficiency of biosorbents (jasmine green tea leaves, genmaicha green tea leaves, salted peanut shells and unsalted peanut shells) on Nickel (II) and Chromium (VI) ions, to study the effects of initial biosorbent dosage and pH on heavy metal removal and to optimize the biosorption condition via Design Expert Software. The prescreening stage proved that jasmine green tea leaves was the most effective biosorbent in removing 90.98% of Chromium (VI) and 96.13 % of Nickel (II) ions. Next, five level full factorial experimental design was used in batch biosorption process to investigate the individual and interactive effects of initial biosorbent dosage and biosorption system pH on the removal of heavy metal ions. According to the ANOVA of the design, initial biosorbent dosage and pH were considered as the significant factor in the removal of Chromium (VI) and Nickel (II) ions by jasmine green tea leaves. The numerical optimization tool provided that 100 % removal of Cr (VI) can be obtained using 2.011 g of jasmine green tea leave with system pH 3, while, 92.42 % removal of Ni (II) can be obtained using 2.000 g of jasmine green tea leave with system pH 7. Characterisation study on the biosorbent of before biosorption and after biosorption were performed using SEM-EDX, FTIR and XRD to detect the presence of heavy metals and changes in physical and chemical properties of the biosorbents. The SEM-EDX showed the large porous structure of the virgin jasmine green tea leaves and confirms the presence of Chromium and Nickel at 00.35 % and 02.02 % after adsorption, respectively. FTIR spectrum showed that hydroxyl, carbonyl and ether group were involved in the uptake of Ni (II), while, hydroxyl, alkene, carbonyl, aliphatic group, carboxyl and ether contributed in the uptake of Cr (VI). Finally, the analysis from XRD depicts that the adsorption of hexavalent chromium and nickel ions transformed amorphous surface of virgin jasmine green tea leaves into crystalline structure along with the increase in crystallite size from 2.1109 nm to 13.7927 nm and 58.8390, respectively. Higher removal efficiency of jasmine green tea leaves was strongly promoted by its large porous structure, high carbonaceous composition and oxygenated functional groups. The initial biosorbent dosage and pH of solution significantly influence the biosorption of Nickel and Chromium.